SPOTS project and development of a standard and reference material - Patterson E.; Burguete R. (EPJ Web of Conferences, 2010)
The ‘Standardization Project for Optical Techniques of Strain measurement’ (SPOTS) was focused on the development of reference materials for calibrating optical systems for static strain measurement and standardized tests for evaluating the capabilities of such systems. The reference material consists of a beam in four-point bending within a monolithic frame that ensures reproducibility of the boundary and loading conditions. A procedure for the use of the reference material has been developed and leads to the evaluation of measurement uncertainties that allow the construction of confidence limits for the data obtained with the calibrated optical system. The design and methodology have been developed into a proposed draft standard which is being endorsed by VAMAS (Versailles Agreement on Materials And Standards) for review by ISO (International Standards Organisation). An overview of philosophy underpinning the proposed draft standard is presented and serves as an introduction to the reference material and standardized test and their use in providing higher confidence in optical measurements of strain.